Transition From Proto-Kranz-Type Photosynthesis to HCO3– Use Photosynthesis in the Amphibious Plant Hygrophila polysperma - Horiguchi, Genki; Matsumoto, Kaori; Nemoto, Kyosuke; Inokuchi, Mayu; Hirotsu, Naoki (Frontiers in Plant Science, 2021)
Hygrophila polysperma is a heterophyllous amphibious plant. Growth of H. polysperma in submerged conditions is challenging due to the low CO2 environment, increased resistance to gas diffusion, and bicarbonate ion (HCO3–) being the dominant dissolved inorganic carbon source. The submerged leaves of H. polysperma have significantly higher rates of underwater photosynthesis compared to the terrestrial leaves. 4,4'–Diisothiocyanatostilbene–2,2'–disulfonate (DIDS), an anion exchanger protein inhibitor, and ethoxyzolamide (EZ), an inhibitor of internal carbonic anhydrase, repressed underwater photosynthesis by the submerged leaves. These results suggested that H. polysperma acclimates to the submerged condition by using HCO3– as a biophysical carbon concentrating mechanism. Additionally, proteome analysis revealed that submerged leaves accumulated fewer proteins associated with C4 photosynthesis compared to terrestrial leaves. This finding suggested that H. polysperma is capable of C4 and C3 photosynthesis in the terrestrial and submerged leaves, respectively. The ratio of phosphoenol pyruvate carboxylase to ribulose 1,5–bisphosphate carboxylase/oxygenase (Rubisco) in the submerged leaves was less than that in the terrestrial leaves. Upon anatomical observation, the terrestrial leaves exhibited a phenotype similar to the Kranz anatomy found among C4 plants; however, chloroplasts in the bundle sheath cells were not located adjacent to the vascular bundles, and the Kranz anatomy was absent in submerged leaves. These results suggest that H. polysperma performs proto–Kranz type photosynthesis in a terrestrial environment and shifts from a proto–Kranz type in terrestrial leaves to a biophysical carbon concentrating mechanism in the submerged environments.